2013
DOI: 10.1007/s00213-013-3247-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of 5-HT7 receptor: effect on object recognition performances in mice

Abstract: These data suggest that 5-HT7R tonically modulates cognitive processes involved in consolidation performances in object recognition. Therefore, 5-HT7R could be a promising target to treat memory dysfunctions (especially episodically related deficits) related to normal or pathological ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…32,33 This appears to be highly important because depressive disorders are often accompanied by cognitive decline. Thus pro-cognitive properties may have some benefit in regard to the treatment of depression.…”
Section: Resultsmentioning
confidence: 98%
“…32,33 This appears to be highly important because depressive disorders are often accompanied by cognitive decline. Thus pro-cognitive properties may have some benefit in regard to the treatment of depression.…”
Section: Resultsmentioning
confidence: 98%
“…The 5-HT7R knock-out mice exhibits specific impairments in contextual learning (Roberts et al, 2004). Several other studies highlight the implication of 5-HT7R in memory and attention-related processes (Gasbarri et al, 2008; Freret et al, 2014; Meneses, 2014), underscoring its role in the modulation of the neuronal network associated with cognitive functions. Therefore, the study of this receptor and its associated intracellular pathways may provide invaluable information for the treatment of learning and memory disorders.…”
Section: The Serotonin Receptor 7 Modulates Connectivity In Adolescenmentioning
confidence: 92%
“…In the CNS the receptor is expressed in the diencephalon, forebrain and in the Purkinje neurons of the cerebellum (for reviews see Matthys et al, 2011; Gellynck et al, 2013). The wide distribution of 5-HT7R in the brain reflects the numerous functions in which this receptor is implicated, such as circadian rhythms, sleep-wake cycle, thermoregulation (Leopoldo et al, 2011; Adriani et al, 2012; Monti et al, 2014; Romano et al, 2014) and nociception (Garcia et al, 2011), but also cognitive functions such as learning and memory processing (Roberts and Hedlund, 2012; Freret et al, 2014; Meneses, 2014). Importantly, the putative involvement of 5-HT7R in many neuropathological processes such as anxiety, schizophrenia, epilepsy, migraine, impulsivity and depression, cognitive and mood disturbances (Hedlund, 2009; Cates et al, 2013; Gellynck et al, 2013), makes it a potential target for new therapeutic applications.…”
Section: The Serotonin Receptormentioning
confidence: 99%
“…Freret et al (2014) reported that with a 2-h delay, (post-training) administration of the 5-HT 7 receptor antagonist SB-269970 (3 and 10 mg/kg, sc) impaired the discrimination of the novel object; but with a 4-h delay, while control mice were not able to discriminate the novel object, mice treated with the agonist 5-carboxamidotryptamine (5-CT; displaying affinity for several receptors including 5-HT 7 ; Hoyer et al, 1994) showed a significant discrimination. This promnesic effect was blocked by SB-269970, but not by WAY-100135 or GR-127935 (5-HT 1A or 5-HT 1B/1D receptor antagonists, respectively; Hoyer et al, 1994).…”
Section: -Ht7 Receptor Stimulationmentioning
confidence: 99%